Relational Contracts in Moral Hazard with Subjective Performance Measures - 이명기 (한국농촌경제연구원, 2007)
This paper analyzes optimal self-enforcing termination contracts under the assumptions that the agent (e.g. grower) must make relationship-specific investments prior to contracting, that the principal (e.g. integrator or processor) has ex post full bargaining power due to monopsony power, and that performance is subjectively measured. In the optimal self-enforcing termination contract, the principal motivates the agent by rewarding the agent through continuation of the relationship for high levels of performance and penalizes the agent through termination for low levels of performance. Performance bonuses are no longer used. When the agent must make relationship-specific investment, the principal may not pay positive rents. This implies that the relationship-specificity of investment increases the principal's expected payoff, whereas it decreases the agent's.
Keywords: relational contract; subjective performance measures; relationship-specific investment; moral hazard; termination contract; relational contract; subjective performance measures; relationship-specific investment; moral hazard; termination contract